The Dovekie, Alle alle, as a Spring Migrant in Eastern Lancaster Sound and Western Baffin Bay - Renaud, Wayne E.; McLaren, Peter L.; Johnson, Stephen R. (ARCTIC, 1982)
The distribution and numbers of dovekies during spring migration were studied by aerial surveys of eastern Lancaster Sound (1976, 1978, 1979) and western Baffin Bay (1978, 1979). Dovekies that nest in northwest Greenland migrated north through the study area during May. Extrapolations of recorded densities indicate that a peak of ~14 million dovekies may have been present in eastern Lancaster Sound and northwest Baffin Bay in mid-May 1978: fewer were present in May 1979, although the migration was more protracted and total numbers migrating through these areas may have been similar. Dovekies preferred offshore pack ice habitats with moderate to heavy ice cover. Possible reasons for the highly variable distributions in the three years are discussed.Key words: dovekie, Alle alle, spring migration, Lancaster Sound, Baffin Bay, aerial surveys